2019
DOI: 10.1002/pbc.28070
|View full text |Cite
|
Sign up to set email alerts
|

The alternative complement pathway activation product Ba as a marker for transplant‐associated thrombotic microangiopathy

Abstract: BackgroundTransplant‐associated thrombotic microangiopathy (TA‐TMA) occurs after hematopoietic stem cell transplantation (HSCT) and is characterized by microvascular thrombosis and end‐organ injury particularly of the kidneys. TA‐TMA is challenging to diagnose and treat, which can lead to long‐term complications and death in patients with severe disease. Studies have shown that genetic abnormalities of the alternative complement pathway (AP) are associated with TA‐TMA. We hypothesized that patients with TA‐TMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Previous studies report an association between TA-TMA and various complement proteins. Recently, Sartain et al reported that Ba might be a diagnostic marker for TA-TMA in pediatric patients (11). They suggested that alternative pathway activation contributes to the pathogenesis of TA-TMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies report an association between TA-TMA and various complement proteins. Recently, Sartain et al reported that Ba might be a diagnostic marker for TA-TMA in pediatric patients (11). They suggested that alternative pathway activation contributes to the pathogenesis of TA-TMA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that human leukocyte antigen (HLA)mismatched donors, conditioning intensity, acute graft-versushost disease (aGVHD), calcineurin inhibitors, and viral infection are risk factors for TA-TMA; thus TA-TMA is a multifactorial and heterogeneous disorder (4)(5)(6). Interestingly, recent studies indicate that the complement system may contribute to development of TA-TMA (7)(8)(9)(10)(11)(12). First, a pediatric cohort suggested an association between genetic abnormalities of complement-related genes and TA-TMA (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although the focus here was on VCA transplants, it is likely B.PSel-Crry would be an equally suitable therapy in solid organ transplantation. Microvascular thrombosis is a common complication early and late post-transplantation (40)(41)(42)(43), particularly in extended criteria donors, and thus application of B.PSel-Crry could represent a novel therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Severe ADAMTS13 deficiency is not a hallmark of TMA-TA; the etiology is thought be related to endothelial damage from chemotherapy and the post-transplant inflammatory state leading to classical and alternative complement activation. 173,176,177 Alterative pathway dysfunction is supported by complement regulatory mutations and anti-factor H antibodies in a subset of patients. 178 TMA-TA also frequently co-occurs with other insults including infection and graft versus host disease so it can be challenging to assess the relative severity of TMA-TA.…”
Section: Clinical Overview Of Microvascular Thrombosismentioning
confidence: 99%